Differentiation of loads in the basic mesocycle according to special physical readiness in young weightlifters of 14-15 years old, taking into account the phases of a specific biological cycle - Lydmila Kanunova; Oleksandr Piven; Evgeny Plotnikov (Kharkiv State Academy of Physical Culture, 2020)
Purpose: to determine the effectiveness of using complexes of strength-oriented exercises in the basic mesocycle according to the special physical readiness of young weight-lifters of 14-15 years old, taking into account the phase of the ovarian-menstrual cycle. Material and methods: in accordance with the methodological approach to solving the problem and the set tasks, the research program included a set of methods: analysis of scientific and methodological literature, determination of special physical fitness with the help of pedagogical testing of young women weights, pedagogical observation of the training process and methods of mathematical statistics. Results: modern approaches are presented regarding the peculiarities of building the training process of young weight-lifters of 14-15 years old, a detailed structure of building a basic mesocycle according to SPP is presented, taking into account the differentiation of the load of special power-oriented complexes in different phases of the ovarian-menstrual cycle. The experiment involved the control and experimental groups, in which they used different approaches to planning the training process and the peculiarity of which is that in the experimental group special complexes of strength preparedness were used, taking into account the efficiency in different phases of the CMC. Conclusions: the introduction of the methodology of the training process of young weightlifters of 14-15 years old in the basic mesocycle of the annual macrocycle, taking into account the phases of the ovarian-menstrual cycle, contributed to a significant increase in the indicators of general and special-auxiliary exercises in the experimental group in relation to the control one in the snatch of 8 kg kettlebells in 10 min ( t = 2.15; p <0.05) in squatting with a 24 kg kettlebell on the shoulders by 10.2 times (t = 2.28; p <0.05) and deadlift - by 6.7 times (t = 2.25; p <0.05).